Оцінка ефективності програми реабілітації психологів сектору безпеки та оборони України - Мілорадова, Н. Е.; Miloradova, N. E.; Доценко, В. В.; Dotsenko, V. V.; Вікторія Доценко; Natalia Miloradova (Вісник Харківського національного університету внутрішніх справ. – 2025. – № 2 (109). - С. 432-443, 2025)
У статті представлено оцінку ефективності програми реабілітації психологів сектору безпеки та оборони України «Шлях до перемоги». Оцінка ефективності програми реабілітації є комплексним процесом, що охоплює аналіз різних аспектів: задоволеності учасників, змін у їхньому психологічному стані (рівень стресу, тривожності, самопочуття, активності), а також застосування набутих знань у професійній діяльності. Результати дослідження демонструють позитивну динаміку: зниження тривожності, покращення самопочуття та загальне підвищення задоволеності програмою. Отримані дані підтверджують ефективність програми реабілітації та її позитивний вплив на психофізичний стан психологів сектору безпеки та оборони.

The article presents an evaluation of the effectiveness of the rehabilitation programme for psychologists in the security and defence sector of Ukraine aimed at restoring the psychological health and professional capacity of specialists working with people who have experienced traumatic events or have psychological problems. The research highlights the critical role of psychologists in the security and defence sector in maintaining the mental health of military personnel and their families, as well as the significant emotional stress that psychologists themselves are exposed to when they are constantly faced with the traumatic experiences of others. Therefore, rehabilitation programmes are extremely important for preventing professional burnout, strengthening personal and professional resilience, acquiring new knowledge and skills in dealing with trauma, improving the quality of psychological care, creating a culture of mutual support and ensuring long-term professional effectiveness. Evaluating the effectiveness of a rehabilitation programme is a complex process that includes an analysis of various aspects: participants’ satisfaction, changes in their psychological state (stress, anxiety, well-being, activity) and the application of the knowledge gained in their professional activities. The study showed positive dynamics in reducing anxiety, improving well-being and overall satisfaction with the programme. The majority of psychologists noted the harmonious combination of leisure and training, the professionalism of the trainers, the favourable atmosphere and the usefulness of the knowledge and skills gained. The results of the psychodiagnostics revealed significant positive changes in the psychological state after completing the programme: there was a decrease in the level of acute stress, improvement in health, activity and mood. In addition, the indicators of reactive and personal anxiety decreased significantly. The assessment of behavioural changes showed that the participants actively apply the acquired knowledge and skills in their professional and personal lives.
Evaluation of the effectiveness of the rehabilitation programme for psychologists in the security and defence sector of Ukraine
Keywords: оцінка ефективності; соціально-психологічна реабілітація; програма; професійне вигорання; стрес; техніки відновлення; evaluation of effectiveness; social and psychological rehabilitation; programme; professional burnout; stress; recovery techniques